Людський капітал в інноваційному розвитку сільських територій України: ментальні аспекти - Крупін, В. Є.; Злидник, Ю. Р. (Видавництво Львівської політехніки, 2013)
Розглянуто роль людського капіталу в процесах інноваційного розвитку сільських територій України. Виділено ментальні особливості наявного людського капіталу в контексті активізації інноваційної діяльності на сільських територіях, основні бар’єри на шляху впровадження інновацій та їхні характеристики. Обґрунтовано ключові риси ментальності сільського населення, необхідні для ефективного розвитку сільських територій на основі інновацій. Виокремлено сутність впливу освіти та інформаційних технологій на формування інноваційної ментальності людського капіталу сільських територій України. The role of human capital in the processes of innovational development in rural areas of Ukraine is reviewed. The mental peculiarities of present human capital in the context of intensification of innovational activity in rural areas, main barriers on the way to innovations’ implementation, as well as their characteristics, are outlined. Key features of the mentality of the rural population, necessary for effective rural development based on innovations, are substantiated. The essence of education and the impact of information technologies on the formation of innovative mentality of human capital in rural areas of Ukraine are singled out.
Human capital in innovational development of rural areas of Ukraine: mental aspects
Keywords: людський капітал; інновації; ментальність; сільські території; Україна; human capital; innovation; mentality; rural areas; Ukraine